Characterization and demulsification of water-in-crude oil emulsions - Nour, A. H. (2007)
Many advances have been made in the field of emulsions in recent years. Emulsion behavior is largely controlled by the properties of the adsorbed layers that stabilized the oil-water surfaces. The effect of chemical demulsifiers in demulsification of water-in-crude oil emulsions were assessed experimentally. The relative rates of water separation were characterized via graduated beakers. Four groups of demulsifier with different functional groups were used in this work namely amines, polyhydric alcohol, sulphonate and polymer. The effect of alcohol addition on demulsification performance also studied. The results obtained in this study have exposed the capability of chemical demulsifiers in destabilization of water-in-crude oil emulsions. Further works are nevertheless required to provide deeper understanding of the mechanisms involved to facilitate the development of an optimum system applicable to the industry.